Exploring the Impact of Transformation to Fully Online Learning During COVID-19 on Malaysian University Students' Academic Life and Performance - Al-Kumaim, Nabil H.; Mohammed, Fathey; Gazem, Nadhmi A.; Fazea, Yousef; Alhazmi, Abdulsalam K.; Dakkak, Othman (International Association of Online Engineering (IAOE), 2021)
The COVID-19 pandemic forced many universities to shift suddenly to fully online learning. This study explores the impact of that transformation on Malaysian university students' academic life and performance. It examines challenges, learning experiences, and perceived effects of online learning during the pandemic period.